Characteristics of biochar from agricultural residues produced by traditional combustion and its potential as a soil amendment - Ali Rahmat; Sukamto Sukamto; Santi Ari Respat; Fera Arum; Wiwiek Dwi Susanti; Yudia Azmi; Zurrahmi Wirda (International Journal of Advances in Applied Sciences, 2026)
Biochar is a carbon-rich material produced through pyrolysis. However, pyrolysis methods that generate high-quality biochar typically require expensive equipment and technical expertise. This study examines the characteristics of biochar produced from rice husk, cassava wood, and corn cobs using a traditional burning method as an alternative to pyrolysis. The research results showed that the carbon content of biochar produced using traditional methods was comparable to, or even higher than, biochar produced using more advanced pyrolysis methods. Corncob biochar had the highest carbon content among all samples. X-ray fluorescence (XRF) analysis revealed that rice husk biochar had the highest silica content, while cassava wood biochar showed higher percentages of calcium (Ca) and magnesium (Mg) than the other biochars. X-ray diffraction (XRD) characterization results indicated a higher degree of graphitic crystallinity in the corncob biochar, while Fourier transform infrared spectroscopy (FTIR) spectra confirmed the presence of hydroxyl groups, aromatic C=C, and cellulose residues in all samples. thermogravimetric–differential thermal analysis (TG-DTA) and differential scanning calorimetry (DSC) analyses provided insights into thermal behavior and carbonization levels, with corncob biochar having the highest carbon content and thermal resistance. The application of biochar to acidic soils has been shown to significantly increase soil pH and organic carbon content. The simple combustion method used in this study is capable of producing biochar with diverse physicochemical properties, thus offering a sustainable approach to soil improvement, increased nutrient retention, and carbon sequestration, while providing added value to agricultural waste and waste valorization strategy.